DOMICILE COMMUNITY ORIENTATION IN REMOTE VILLAGE (DESCRIPTIVE STUDY IN NEGERI GUGUNG VILLAGE, SUBDISTRICT SIBOLANGIT, DELI SERDANG REGENCY) - DESTI ARIANI (Departemen Sosiologi Universitas Sumatera Utara, 2012)
ABSTRACT Writing a scription entitled